2016
DOI: 10.1186/s13058-016-0792-3
|View full text |Cite
|
Sign up to set email alerts
|

Involution of breast tissue and mammographic density

Abstract: BackgroundMammographic density decreases and involution of breast tissue increases with age; both are thought to be risk factors for breast cancer. The current study investigated the relationship between involution or hormone treatment (HT) and breast density among multiethnic patients with breast cancer in Hawaii.MethodsPatients with breast cancer cases were recruited from a nested case-control study within the Multiethnic Cohort. HT use was self-reported at cohort entry and at the time of the density study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…In a recent study using data from The Breast Radiology Evaluation and Study of Tissues Stamp Project (Stamp), where benign biopsy tissues were annotated with more standardized and quantitative TDLU measures, the association of dense breast tissues with lower extent of TDLU involution was confirmed . In contrast, a report from Multiethnic Cohort showed that greater TDLU involution assessed in adjacent non‐tumor breast tissue was associated with a larger MD area . There may be several reasons to explain these conflicting results, such as the heterogeneity in the assessment of TDLU involution (standardized quantitative vs .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study using data from The Breast Radiology Evaluation and Study of Tissues Stamp Project (Stamp), where benign biopsy tissues were annotated with more standardized and quantitative TDLU measures, the association of dense breast tissues with lower extent of TDLU involution was confirmed . In contrast, a report from Multiethnic Cohort showed that greater TDLU involution assessed in adjacent non‐tumor breast tissue was associated with a larger MD area . There may be several reasons to explain these conflicting results, such as the heterogeneity in the assessment of TDLU involution (standardized quantitative vs .…”
Section: Discussionmentioning
confidence: 99%
“…4 Contrary to these reports, a recent analysis of breast cancer cases within the Multiethnic Cohort, which was highly enriched for Japanese Americans (43%) and included participants who were older (mean age 59.7 years) and thinner than in other studies showed the opposite direction of the association (i.e., greater TDLU involution associated with higher dense area). 6 The explanation of this finding is unresolved but may suggest potential racial variation in the TDLU-MD relationship.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations